An enhanced business model of University Teknologi Malaysia as university of the future - Salman, Nik Nabilah Farihin Hani; Norazmi, Nurul Ainna Syuhada; Zulkifli, Nurul Asyiqin; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
Higher education enrolment has increased by 70% to 1.2 million students over the last 10 years. The growth rate of research output and quality has been one of the highest in the world, and Malaysian institutions are ranked strongly amongst its Asian peers. Malaysia is also now a top 10 destination for international students. Malaysia’s Prime Minister has mentioned that education has been key to the country’s national development by 2020 by increasing both access to and quality of higher education. Universiti Teknologi Malaysia (UTM) is taken as a case study, as it is one of the Malaysian top ranking universities in understanding its transformation plan, game changers and key project in transforming digitally the university to the University of the Future. Literature review and business model canvas framework is used in this paper. The key contribution of this paper is an enhanced business model of UTM as the University of the Future.